Pembelajaran Pemahaman Konsep Fungsi Komposisi - Ananda Geno; Bella Triandini; Khairulanshari Khairulanshari (Lembag, 2024)
Mathematics is one of the compulsory subjects that students must master. However, in reality, many students do not understand this compulsory subject. This research aims to help describe the understanding of the concept and solve the concept of function composition. This research is a qualitative research that can be used as a reference for students of SMAN 17 Pekanbaru to find out their understanding of the concept in solving function composition problems.The author will explain in this scientific journal what is the definition of function composition, properties of function composition, how the multiplication and division of functions and addition and subtraction of functions are formed. This can help describe the understanding of the concept and solve the function composition.